"PLAYFUL MATHEMATICS: A REFLECTION ON ITS PRESENCE IN THE CLASSROOMS OF THE LAS TABLAS DISTRICT" - Vargas, Carlos; Cedeño, Eliecer; Medina, Alcibíades; Galástica, Narciso (Seven Editora, 2025)
This research examines the use and perception of playful mathematics in elementary schools in the Las Tablas district of Panama, an area lacking systematic studies on the topic. Using a mixed-methods approach (surveys, interviews, and classroom observations), the study collected data from 50 teachers and a group of students from Presidente Porras and Claudio Vásquez schools. The findings show an overwhelmingly positive perception of playful mathematics. Teachers and students believe that games and interactive activities not only make learning mathematics more engaging and fun, but also improve the understanding of complex concepts. The study highlights that 94% of teachers observe improved academic performance in students who participate in these activities. Similarly, a large majority of students report that playful activities improve their enjoyment of class and make them more engaged. Despite positive feedback, the article identifies implementation challenges, such as the risk of student distraction from the game and resource and time constraints. The results suggest that, while the methodology is present, its effective implementation requires a careful balance between the game and the educational content. The study concludes that gamified strategies are an effective and well-received pedagogical tool that could benefit from increased teacher training and resources to optimize their impact on mathematics learning.DOI: https://doi.org/10.56238/sevened2025.030-078